2001
DOI: 10.1104/pp.126.2.536
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Accumulation Patterns of Transparent Testa Mutants of Arabidopsis

Abstract: Flavonoids have been implicated in the regulation of auxin movements in Arabidopsis. To understand when and where flavonoids may be acting to control auxin movement, the flavonoid accumulation pattern was examined in young seedlings and mature tissues of wild-type Arabidopsis. Using a variety of biochemical and visualization techniques, flavonoid accumulation in mature plants was localized in cauline leaves, pollen, stigmata, and floral primordia, and in the stems of young, actively growing inflorescences. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
268
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(292 citation statements)
references
References 37 publications
19
268
2
3
Order By: Relevance
“…4). Amazingly, the same root regions with GUS activity accumulate both flavonoids and auxins (Murphy and Taiz, 1999;Murphy et al, 2000;Peer et al, 2001;Ljung et al, 2005). In this context, it should be stressed that, in Arabidopsis roots, ChS and chalcone isomerase (Saslowsky and Winkel-Shirley, 2001) are located in sites where the PvACCase gene promoter is active (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Amazingly, the same root regions with GUS activity accumulate both flavonoids and auxins (Murphy and Taiz, 1999;Murphy et al, 2000;Peer et al, 2001;Ljung et al, 2005). In this context, it should be stressed that, in Arabidopsis roots, ChS and chalcone isomerase (Saslowsky and Winkel-Shirley, 2001) are located in sites where the PvACCase gene promoter is active (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that PvACCase::GUS transgene expression during development has a strong correlation to the tissues where auxins are accumulated in Arabidopsis. For example, several studies have shown high auxin concentrations in Arabidopsis hydathodes, stipules, and root tips; furthermore, flavonoids colocalize with zones of auxin accumulation (Murphy et al, 2000;Peer et al, 2001;Aloni et al, 2003). To determine auxin responsiveness of the PvACCase gene promoter, 8-dold roots were treated with IAA.…”
Section: Pvaccase Response To Exogenous Auxin Applicationmentioning
confidence: 99%
“…It is not clear if SfN8DT-1 catalyzed the prenylation of kaempferol in planta, or if naringenin, a precursor of kaempferol, was first prenylated by SfN8DT-1 and then converted to 8DK in vivo. However, because kaempferol is the major flavonoid in Arabidopsis and the in vivo level of naringenin is very low, the occurrence of 8DK may be reasonable (Peer et al, 2001). The detection of an appreciable amount of 8DN in naringenin-fed transgenic Arabidopsis indicated that SfN8DT-1 was enzymatically functional in planta and contributed to the formation of prenylated flavonoids in a heterologous plant.…”
Section: Table II Production Of Prenylated Flavonoids In Transgenicmentioning
confidence: 99%
“…DPBA fluorescence is the only technique that allows quantification of flavonoid abundance at a tissue-specific level. Furthermore, it has been shown in several reports that DPBA fluorescence accurately reports flavonoids as detected by microspectrofluorometry, HPLC, or mass spectroscopy (Mathesius et al, 2000;Peer et al, 2001).…”
Section: Acc Induces Flavonoid Accumulationmentioning
confidence: 99%
“…Flavonoid accumulation was visualized in vivo by the fluorescence of flavonoid-conjugated DPBA after excitation with blue light (488 nm; Sheahan and Rechnitz, 1992;Murphy et al, 2000;Peer et al, 2001;Buer and Muday, 2004). Assays to determine the effect of ACC on DPBA fluorescence accumulation were performed by transplanting 5-d seedlings to control media or media containing 2.5 mM ACC and incubating for the required times before staining with DPBA and measuring intensities as described below.…”
Section: Flavonoid Fluorescence Staining and Quantificationmentioning
confidence: 99%